UPAYA MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPLANASI DAN HASIL BELAJAR BAHASA INDONESIA DENGAN METODE INKUIRI PADA SISWA KELAS XI IPS 1 SMA NEGERI 3 METRO - Cik Ayu Kesuma (LPPM STKIP PGRI Bandar Lampung, 2020)
This study aims to describe the improvement of skills and learning outcomes of Indonesian language, especially writing explanatory text for class XI IPS 1 SMA Negeri 3 Metro using the inquiry method. The research design used was classroom action research. Methods and data collection tools using test and non-test techniques (observation, documentation, and interviews). The results showed an increase in explanatory text writing skills in the pre-cycle an average of 79.25%, in the first cycle it became 96.83, in the second cycle the explanatory text writing skill was 108.91, and the third cycle was 200.16. The increase in pre-cycle 17.25%, cycle II to 12.08% and to cycle III to 91.25%. Furthermore, the average pre-cycle Indonesian learning outcomes were 5, cycle I got an average of 7, cycle II became 8, and cycle III became 9. The increase in pre-cycle to cycle I was 2%, cycle I to cycle II was 1%, cycle II to cycle III to 1%.